A study of the awareness of reading strategies of form five students in SMK Raja Permaisuri Bainun, Ipoh, Perak / Noriah Yeop Nordin - Yeop Nordin, Noriah (2010)
Meta-cognitive awareness has become an important concept in the teaching of reading, primarily because evidence suggests that meta-cognitive awareness of reading strategy use can improve and enhance reading comprehension. Thus, the study was discussed on the awareness of meta-cognitive strategies of eighty-four (84) Form Five students in a boarding school in Ipoh, Perak. A mixed mode research method comprised of both quantitative and qualitative data was employed to investigate the meta-cognitive awareness of reading strategies of Form Five students. A survey questionnaire consisted often (10) items on demographic profiles and thirty (30) items on Survey of Reading Strategies (SORS) based on the three types of strategies types - Global Reading, Problem-Solving and Support Reading Strategies were administered to the students. Open-ended questions in the interview were used for the qualitative data as a mean of tri angulation. The findings of the study showed that all of the subjects were meta-cognitively aware of the reading strategies. This showed that the subjects had a strong awareness on using effective strategies. The results also showed that there were significant different between males' and females' level of meta-cognitive awareness of reading strategy used and their achievement in English PMR grades. The overall results also indicated that the Form Five students generally had positive attitude towards reading as they rated themselves as good and confident readers, good feelings towards reading as well as having clear conceptual understanding of reading. Finally, this research proposed some recommendations for pedagogical practices and future research.